The problem seems to be ambiguous notation.
Without more parentheses, it is unclear whether your
y=f(x+5/2) is
y = f[(x+5)/2]
or
y = f[x + (5/2)]
They are not the same thing.
One of those agrees with your teacher's
f[(1/2)(x+5)]
y=f(x+5/2)
I timesd x+5 by 2 to get rid of 2 at the bottom and timesd y by 2. Then to get rid of 2 from y i divided it, and i got this.
y=1/2f(x+5)
however my teacher got y=f(1/2(x+5))
what did i do wrong?
3 answers
The question in my book only has brackets around (x+5/2)
I still don't understand the whole process